'A Safer Ramadan': developing an integrated approach to support safer fasting and feasting for people with type 2 diabetes. (September 2014) - Daly, H; Byrne, J; Martin‐Stacey, L; Mandalia, P; Carey, ME; Hadjiconstantinou, M; Hassanein, M; Mehar, S; Khunti, K; Davies, MJ
Abstract In the United Kingdom, it is estimated that there are over 300 000 Muslim people with diabetes. Observance of Ramadan is an integral part of being a Muslim that involves abstinence from food and drink from dawn till dusk. In the UK over the next 10 years, Ramadan will fall in the heart of the summer months, resulting in longer fasting periods. For people with diabetes fasting can be problematic, yet few individuals receive advice from health care professionals on how to manage their diabetes during the Ramadan period. A 'whole systems' approach, involving community awareness, health care professional training and patient education, was used to develop and implement an educational intervention to address the needs of individuals with type 2 diabetes during the Ramadan period. This practice point paper details this service improvement project and lists a number of recommendations to improve the uptake and sustainability of such interventions to support safer fasting and feasting for people with type 2 diabetes during religious events. Copyright © 2014 John Wiley & Sons, Ltd.